The Qijurittuq site (IbGk-3), Eastern Hudson Bay: An IPY Interdisciplinary Study - Despriée, Jackie; Voinchet, Pierre; Tissoux, Hélène; Moncel, Marie-Hélène; Arzarello, Marta; Robin, Sophie; Bahain, Jean-Jacques; Falguères, Christophe; Courcimault, Gilles; Dépont, Jean; Gageonnet, Robert; Marquer, Laurent; et al. (Geografisk Tidsskrift-Danish Journal of Geography, 2010)
International audience An interdisciplinary study was conducted at Qijurittuq (IbGk-3), an archaeological site located on Drayton Island along the eastern shore of Hudson Bay, Nunavik. Local Inuit made important contributions to the research. High school students participated in the field school, and elders shared their traditional knowledge. The elders expressed an interest in the source of the wood used to construct Qijurittuq's semi-subterranean dwellings, and this inspired us to expand our research in that direction. This interdisciplinary study included a reconstruction of the geomorphological and environmental history of Drayton Island, wood provenance and dendrochronology studies, research on house architecture and settlement patterns, and a zooarchaeological analysis. This paper synthesizes the preliminary results of this interdisciplinary investigation within the context of climate change. We discuss the persistence of semi-subterranean dwellings in eastern Hudson Bay long after they had been abandoned elsewhere. At Qijurittuq, their abandonment corresponds with the end of Little Ice Age. However, at the same time, the development of more permanent contact with Euro-Canadians was having a strong impact upon Inuit culture.